RESEARCH OF METHODS AND ALGORITHMS FOR AUTOMATIC DETECTION OF THE PRESENCE OF COMBUSTION OF THE FUEL-AIR MIXTURE IN THE AFTERBURNER COMBUSTION CHAMBER OF GAS TURBINE ENGINES - Vyhaniailo, Ya. M.; Shilo, G. M. (Computer Science and Applied Mathematics, 2024)
The article provides an overview of the existing systems and methods for detecting the presence of flame in the afterburner combustion chamber (ACC) of aircraft gas turbine engines. They are classified by the operating principle. A detailed description of the main properties and analysis of the features of each system are presented. The need to improve the currently known systems for detecting the presence of flame in the ACC is indicated in connection with the need to increase the accuracy and speed of detecting the combustion of the fuel-air mixture in the ACC in the entire altitude-speed range of gas turbine engine operation. The design features of the ACC, which are being developed by Ukrainian engine builders, are described, and it is explained why it is impossible to use known and traditional methods of determining the presence of flame for such ACC design. It is concluded that the existing methods for detecting the presence of flame have limitations in the possibility of application and a significant probability of erroneous responses, so there is a need to develop a new method and algorithms for reliable detection and control of the combustion of the fuel-air mixture in the ACC. The most promising direction of development of systems and methods for determining the presence of flame in the ACC is determined. This is the analysis of the state of the environment in the ACC using microprocessor technology, using such flame properties as electrical conductivity due to the presence of ions and radicals, and the presence of conductivity pulsations in certain frequency spectra due to the occurrence of oxidation-reduction reactions. The main tasks of the algorithm for analyzing the state of the environment in the ACC based on the parameters of the ionization current between the ionization probes (housing and signal) installed in the ACC are described. A structural diagram of a new microcontroller system for determining and monitoring combustion of the fuel-air mixture in the ACC is proposed. The microcontroller system adjusts the gain factor of the signal from the ionization probes based on the ionization current valueисследование, analyzes the signal spectrum by frequency, and, based on the data received, generates a signal about the presence or absence of combustion of the fuel-air mixture in the ACC.